(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the knowledge of patients with chronic obstructive pulmonary disease undergoing treatment at the Department of Respiratory Medicine, E Hospital, in 2025. Subjects and methods: A cross-sectional descriptive study with analytical components was conducted on 80 chronic obstructive pulmonary disease patients receiving treatment at the Department of Respiratory Medicine, E Hospital. Using the BCKQ instrument. Results: The study revealed that the mean total knowledge score among 80 chronic obstructive pulmonary disease patients was 33.71 ± 6.38 points out of a maximum of 65 points, indicating a moderate level of overall knowledge. Patients demonstrated relatively good understanding of disease etiology (3.73 ± 1.22 points), clinical symptoms (3.65 ± 0.91 points), epidemiology (3.48 ± 1.26 points), and the benefits of smoking cessation and vaccination. However, knowledge regarding medication use remained limited, especially concerning inhaled corticosteroids (0.90 ± 1.13 points) and oral corticosteroids (1.47 ± 1.17 points). In addition, patients’ understanding of dyspnea symptoms, acute exacerbations, and antibiotic use was inadequate. Conclusion: The findings underscore the need to strengthen health education, particularly focusing on proper medication use and the identification of warning signs in chronic obstructive pulmonary disease management.